Realism in Urdu Literature - Jaffar, Muhammad Ramzan; Jan, Ambreen Tabasum Shakir (sourcecoder, 2024)
Realism means presenting external facts with objectivity. This world is completely different from the imaginary world. A realist writer always portrays the present ,having no concern with past complications or dilemmata. The facts he sees are embellished in his writings. Whatever happens to the contrary, does not matter for a realistic author In romantic literature, realism is seen in different ideas, concepts and feelings. The reason for the romanticism found in the poet's poetry is to express his feelings of love that reflects his passion and devotion. Gorky mentions romanticism and realism under the two gradients of literature. Highlighting the life of people and the true reality found in it is the actual concept of realism.